The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1177/1468798415602050
|View full text |Cite
|
Sign up to set email alerts
|

The early Spanish and English writing development of simultaneous bilingual preschoolers

Abstract: This qualitative study investigated the progression in the biliterate levels of conceptualization about writing in Spanish and English of 28 simultaneous bilingual preschoolers. Using a constructivist framework, a holistic bilingual and translanguaging perspective, this qualitative study examined the children’s understanding of the nature of writing in Spanish and English as demonstrated in their written productions and interpretation of their own texts as well as how such understanding develops over time. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Although multilingual students' writing and code-meshing have been the focus of recent research (Gillanders, 2018;Miller & Rowe, 2014;Soltero-González & Butvilofsky, 2016), teachers may be less familiar with how to integrate code-meshing into writing instruction. In the next section, we offer classroom examples of multilingual students' code-meshing.…”
Section: Code-meshing As a Translanguaging Practicementioning
confidence: 99%
“…Although multilingual students' writing and code-meshing have been the focus of recent research (Gillanders, 2018;Miller & Rowe, 2014;Soltero-González & Butvilofsky, 2016), teachers may be less familiar with how to integrate code-meshing into writing instruction. In the next section, we offer classroom examples of multilingual students' code-meshing.…”
Section: Code-meshing As a Translanguaging Practicementioning
confidence: 99%
“…Bialystok found that bilingual preschoolers acquire this notion earlier than monolinguals. Other studies have found that the development of initial levels of conceptualization of writing (i.e., the notion that writing is different from drawing and that writing should be in straight lines) are similar for both monolingual and bilingual children (Gillanders, Franco, Seidel, Castro, & Méndez, ; Soltero‐González & Butvilofsky, ). However, when children begin to understand the connections between graphemes and sounds, more differences between monolinguals and DLLs are evident.…”
Section: Children's Levels Of Conceptualization In Writing In Spanishmentioning
confidence: 98%
“…In another example, a child explained that uppercase and lowercase letters indicated the language used to write each word. Soltero‐González and Butvilofsky () found that in a sample of Spanish–English bilinguals, when writing in Spanish, children tended to use conventional letters, but when writing in English, they used cursive writing, scribbles, zig‐zag shapes, and longer strings of characters.…”
Section: Observing Writing Development In Dllsmentioning
confidence: 99%
See 1 more Smart Citation
“…Translanguaging applies a holistic perspective on bilingualism to pedagogy. Important research on pedagogical aspects of translanguaging have included studies of the ways in which students use their two languages in combination to support bilingual acquisition in small group activities (Martin‐Beltrán, 2014), teachers’ dynamic and interactive use of two languages in classroom instructional settings (Palmer, Martínez, Henderson, & Mateus, 2014), the effects of using two languages concurrently in the teaching of reading (Soltero‐González & Butvilofsky, 2015; Soltero‐González, Sparrow, Butvilofsky, Escamilla, & Hopewell, 2016), among many others. Researchers have used a variety of terms to describe language mixing in classroom contexts, including translanguaging (Durán & Palmer, 2013; García, 2009; Gort, 2015; Gort & Sembiante, 2015; Henderson & Palmer, 2015; Hornberger & Link, 2012; Martin‐Beltrán, 2014; Martínez, Hikida, & Durán, 2015; Martínez‐Roldán, 2015; Palmer et al., 2014; Sayer, 2013; Smith & Murillo, 2015), hybrid language practices (Gutieírrez, Baquedano‐López, & Tejeda, 1999; Gutiérrez, Bien, Selland, & Pierce, 2011; Palmer & Martínez, 2013), holistic bilingualism (Soltero‐González, 2009; Soltero‐González & Butvilofsky, 2015; Soltero‐González et al., 2016; Soltero‐González, Escamilla, & Hopewell, 2011), and codeswitching (Cook, 2001; Fuller, 2009, 2010; Gort, 2012; Martínez, 2010; Moschkovich, 2007; Nava, 2009; Palmer, 2009; Reyes, 2004; Shin, 2005), following the foundational work of Jacobson (1978, 1981, 1990), Milk (1986, 1990), and Faltis (1989, 1990, 1996).…”
Section: Aspects Of Translanguagingmentioning
confidence: 99%